(untitled) (Journal of Hama University, 2022)
The current research aimed to reveal the degree of prevalence of developmental learning difficulties among kindergarten and the level of knowledge of kindergarten teachers about the methods of treating them in Hama Governorate. The research sample consisted of (40) female teachers who were randomly selected from among (246) male and female children of Riyadh. To achieve the goal of the research, a questionnaire consisting of (47) items was used to reveal the degree of prevalence of developmental learning difficulties among Riyadh children, and a questionnaire dedicated to Riyadh teachers to know their level of knowledge of methods of addressing these difficulties, consisting of (48) items . The research concluded with the following results 1-The degree of prevalence of developmental learning difficulties among kindergarten children was (14%) 2-The level of knowledge of Riyadh teachers about methods of dealing with developmental learning difficulties was medium . 3-There are no statistically significant differences in the sample estimates of the parameters according to the educational qualification variable . 4-There are no statistically significant differences in the estimations of the sample parameters according to the variable number of years of experience .